The Contestation of the Malay Marriage in Kepulauan Riau Based on Maqāṣid Sharīah Perspective - Saiin, Asrizal; Umar, M. Hasbi; Badarussyamsi, Badarussyamsi (Universitas Teuku Umar, 2023)
This paper discusses the Malay marriage procession that must be followed by the Malay indigenous people in Kepulauan Riau, because there are moral sanctions if they do not follow applicable customary law. In this study, the problem is examined from the maqāṣid sharīah perspective. The research method used is a qualitative research method in the form of field research. While the nature of the research is descriptive-philosophical, with data sources divided into two, namely primary data sources and secondary data sources. In collecting data, the methods used are observation, interviews, and documentation. The results of this study found that in maqāṣid sharīah perspective, the Malay marriage procession in Kepulauan Riau must be seen based on the level of urgency, namely dharuriyyah, hajjiyyah and tahsiniyyah. If viewed through maqāṣid sharīah perspective, the Malay marriage procession in Kepulauan Riau is something that is characteristic tahsiniyyah. This is because the Malay marriage procession in Kepulauan Riau only serves as a support for increasing a person’s association in society and as a mere form of obedience.